Dėl vieno posesyvumo raiškos atvejo senuosiuose raštuose - Maskuliūnas, Bronius (Baltistica, 2000)
On one case of the expression of possessivity in Old Lithuanian writingsThe paper discusses the expression of possessivity by means of the construction ‘the verb to be + Adessive’. This construction is semantically synonymous with a similar Dative construction and they both express the relation of possession.Because postpositions are etymologically and semantically related to prepositions, the discussed Adessive construction correlates with the construction ‘the verb to be + preposition prie(g) + Dative’.Most of the constructions under discussion have been found in Daukša‘s ‘Postilė’. The fact that Daukša uses the Adessive case interchangeably with a prepositional construction in the same situations to express the same meaning can be explained by the influence of the original construction and the requirements of style.In modern Lithuanian the investigated form of the expression of possession has been substituted for by other means of expression, most frequently by a construction with the verb have. The disappearance of the construction ‘Adessive + to be’ is another proof of the evolution of the expression of possession in Lithuanian from ‘E-languages’ towards ‘H-languages’.
Keywords: lietuvių kalba; senieji raštai; posesyvumas